Evaluation of the child-friendly school program based on the “5s” culture at Ngupasan Elementary School, Yogyakarta: evaluative research using the CIPP model - Martaningsih, Sri Tutur; Nur Fadhilah, Siti (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
Bullying cases in elementary schools still occur frequently, threatening students' sense of security and learning comfort. Child-friendly schools (CFS) play an important role in overcoming violence in schools, but their implementation requires commitment from various parties. This study aims to evaluate the implementation of the CFS program based on the "5S" culture at Ngupasan Public Elementary School, Yogyakarta. This study uses an evaluative approach with the CIPP method and qualitative descriptive analysis. Data were collected through observation, documentation, and interviews, and their validity was tested with triangulation of techniques and sources. Data analysis was carried out using the Miles and Huberman model, including data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the CFS policy has been stated in the vision, mission, and PSAK Decree, but clearer operational regulations are still needed. From the input aspect, facilities and infrastructure have been available, and "5S"-based learning planning has begun to be implemented, although teacher training in developing teaching modules still needs to be improved. From the process aspect, student participation, external support, and implementation of "5S"-based learning have gone well. In conclusion, the CFS program produces better-trained educators and encourages students' social development. The contribution of this research shows that SRA has the potential to increase awareness of school residents in creating a safe environment, preventing violence, and strengthening cooperation between schools, parents, and the community to improve the quality of education.